On the contribution of yarn–yarn slippage to woven fabric failure. Issue 11 (2nd November 2019) - Triki, Ennouri; Dolez, Patricia
Abstract: Failure of woven fabrics involves an interaction between yarns, which can be predicted by yarn slippage. To investigate the contribution of yarn slippage to the failure, we analyzed the relation between various failure properties and critical slippage force ( FS ) using plain and twill weaves of fabrics with different characteristics. Results show that FS increases with yarn density and yarn linear density. The properties in tension for fabrics with different weaves, yarn density, and yarn linear density superimpose on master curves described by a linear relationship when expressed as a function of FS . The same linear behavior is observed when the critical jamming force of yarns expressed as a function of FS . For the tearing energy, a master curve is also obtained when expressed as a function of FS ; however, the curve has a polynomial shape. FS thus appears as a valuable tool to predict the onset of damage in fabrics.